Production by Lintnerization-Autoclaving and Physicochemical Characterization of Resistant Starch III from Sago Palm (Metroxylon sagu rottb) - Wiwit Sri Werdi Pratiwi; Anil Kumar Anal; Surya Rosa Putra (Indonesian Journal of Chemistry, 2015)
Indonesia is one of the biggest central distributions of sago starch. There are some characteristics of sago starch which make it difficult to use in variation of foods. In this study, resistant starch type III (RS3) was produced from sago starch by using lintnerization-autoclaving (LA). Physicochemical characterizations of RS3 were compared by native sago starch (NA), hydrolyzed starch by distilled water (DW) and lintnerized starch (L). Amylose content decreased after hydrolyzed by DW and L, but increasing by using LA. Protein and fat contents decreased after hydrolysis, but crude fiber content increasing, the highest value was obtained lintnerized-autoclaved starch. Lintnerized-autoclaved starch has more compact and rigid structure. The RVA viscosity, swelling power and water holding capacity values reduced after all treatments. Oil in water emulsions were also analyzed by mixture of RS3 and emulsifier (casein or SPI). Viscosities of emulsions from RS casein were lower than those of RS-SPI. Emulsion capacity and emulsion stability values were better gotten using RS-SPI than RS-casein. The highest of emulsion capacity was obtained 11.33%. For storage period, the lowest peroxide and anisidine values of mixture RS-emulsifier were resulted from 5% emulsifier + 5% RS + 5% fish oil.